Evil. Season three [videorecording (DVD)] - King, Michelle (Television producer); King, Robert (Screenwriter) (CBS Studios Inc. ; Paramount, 2022)
Say your prayers and freshen up on your science because Evil returns for a third season. There is plenty to take in including Kristen and David's escalating attraction, creepy toys, some new demons, and the return of everyone's favorite night terror, George. This three-disc collection comes with all ten episodes and deleted scenes.